Phylogenetic and geographical analysis of a retrovirus during the early stages of endogenous adaptation and exogenous spread in a new host. Issue 11 (30th December 2020) - Quigley, Bonnie L.; Wedrowicz, Faye; Hogan, Fiona; Timms, Peter
Abstract: Most retroviral endogenization and host adaptation happened in the distant past, with the opportunity to study these processes as they occurred lost to time. An exception exists with the discovery that koala retrovirus (KoRV) has recently begun its endogenization into the koala ( Phascolarctos cinereus ) genome. What makes this opportunity remarkable is the fact that Northern Australian koalas appear to be undergoing endogenization with one KoRV subtype (KoRV‐A), while all subtypes (KoRV‐A‐I) coexist exogenously, and Southern Australian koalas appear to carry all KoRV subtypes as an exogenous virus. To understand the distribution and relationship of all KoRV variants in koalas, the proviral KoRV envelope gene receptor binding domain was assessed across the koala's natural range. Examination of KoRV subtype‐specific proviral copy numbers per cell found that KoRV‐A proviral integration levels were consistent with endogenous incorporation in Northern Australia (southeast Queensland and northeast New South Wales) while revealing lower levels of KoRV‐A proviral integration (suggestive of exogenous incorporation) in southern regions (southeast New South Wales and Victoria). Phylogeographical analysis indicated that several major KoRV‐A variants were distributed uniformly across the country, while non‐KoRV‐A variants appeared to have undergone lineage diversification in geographically distinct regions. Further analysis of the major KoRV‐A variants revealed a distinct shift in variant proportions in southeast New South Wales, suggesting this as the geographical region where KoRV‐A transitions from being predominantly endogenous to exogenous in Australian koalas. Collectively, these findings advance both our understanding of KoRV in koalas and of retroviral endogenization and diversification in general. Abstract : see also the Perspective by Elliott S. Chiu and Roderick B. Gagne.